Factors influence sexual behavior in adolescent: a literature riview - Puspita Ningrum; Kusbaryanto Kusbaryanto (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: Adolescence is a period where there is a change in transition between childhood and adulthood. Sexual behavior is one form of adolescents committed during the transition. Adolescent sexual behavior is a form of sexual drive or a desire that is done by both men and women. Sexual behavior by an average adolescents is a form of desire and curiosity from adolescents.Aim: This study aims to describe what factors influence adolescent sexual behaviorMethod: This research is a literature review research. The source obtained was taken from several databases such as Google Scholar, found 7,130 journals, 311,653 ProQuest, 2,318,728 PubMed. Based on the overall database data, only 8 journals met the inclusion criteriaResults: Factors of sexual behavior in adolescents in 8 journals discussing peers, male gender is more likely to engage in sexual behavior compared to women, authoritarian parenting style, parental consent about sexual access and perceptions of norms of people around adolescents themselves, families, school media and the community are significantly related to adolescent sexual experiences.Conclusion: Based on the results of the 8 journals, the factors that greatly influence adolescent sexual behavior are the countryside and the media. These findings have many implications for health workers, especially community educators, to implement and develop interventions to prevent sexual risk behaviors.